2022
DOI: 10.3390/jcdd9100342
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Estimated LDL Cholesterol Equations with Direct Measurement in Patients with Angiographically Confirmed Coronary Artery Disease

Abstract: Our goals in the study were to (1) quantify the discordance in LDL-C levels between equations (the Friedewald, Sampson, and Martin/Hopkins equations) and compare them with direct LDL-C (dLDL-C); and (2) explore the proportion of misclassified patients by calculated LDL-C using these three different equations. Methods: A total of 30,349 consecutive patients with angiographically confirmed coronary artery disease (CAD) were prospectively enrolled. Concordance was defined as if the LDL-C was <1.8 mmol/L with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A good deal of external validations confirm that Martin/Hopkins equation outperforms others in accuracy. 11 24 26 27 28 29 30 31 32 33 34 35 36 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A good deal of external validations confirm that Martin/Hopkins equation outperforms others in accuracy. 11 24 26 27 28 29 30 31 32 33 34 35 36 …”
Section: Methodsmentioning
confidence: 99%
“…Many external validation studies have been conducted and showed superiority of the Martin/Hopkins 11 24 26 27 28 29 30 31 32 33 34 35 36 or NIH Equation 2 25 27 37 38 in relation to the Friedewald formula. Here, the purpose of this study was to assess the practical differences 39 40 in LDL-C estimates calculated by Friedewald, Martin/Hopkins, or NIH equation 2 in a population-based, random-sampled, noninstitutionalized general U.S. sample.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has further highlighted the inaccuracy in using LDL-C as a marker for starting or monitoring treatment. Shi et al demonstrated that the level of LDL-C measured in some of the most commonly used calculations can lead to a more than 20% underestimation compared to direct measurement methods, and this was more significant in patients with high TG [ 14 ]. The atherogenic risk of TG is related to the presence of high values of remnant-C, which plays a crucial role in atherogenesis and inflammation.…”
mentioning
confidence: 99%